Factors affecting growth in Indonesian islamic banking industries - Muhammad Bahrul Ilmi (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2022)
Indonesia is becoming one of the powerhouses of Islamic banking and finance globally. Currently, there are 34 Islamic banks in Indonesia. The number of Islamic banks grew gradually, with 12 full-fledged and 22 Islamic Bank Windows. However, the development of Islamic banks is not growing enough compared to conventional banks' growth in Indonesia. The phenomenon of Indonesian Islamic banking growth continues to be an exciting topic in this study. It is worthy of further discussion and study due to its dominance within the Islamic finance market. Accordingly, this study investigates Indonesian Islamic banks' growth based on the phenomenon and lack of literature from an organisational growth perspective. Therefore, the need to investigate Islamic banking growth was triggered by a lack of research to examine the declining growth of Islamic banking in Indonesia over the last 30 years. The study's objective is to expose the root causes of Indonesian Islamic banking's stagnancy from accounting and governance perspectives. This study examines relevant contingent factors of organisational growth in Indonesian Islamic banks, including organisational climate, service orientation, corporate governance, intellectual capital, and regulation. This study combines primary and secondary data analysis to create a comprehensive Indonesian Islamic bank model. It attempts to develop a model for analysing Indonesian Islamic banks' growth based on an organisational perspective. For secondary data, this study uses Islamic banks' annual reports from 2016 to 2018 drawn from the Financial Service Authority database and the websites of each Islamic bank. Furthermore, the research instrument for primary data is a questionnaire survey, with the target respondents being managers of Islamic banks in Indonesia. The managers are respondents as they are best positioned to provide evidence regarding Islamic banks' growth factors. According to the first model's result, only board independence and intellectual capital were accepted to determine an Indonesian Islamic bank's growth. The result of path analysis shows that service orientation has a significant indirect effect on mediating organisational climate and Islamic banks' growth. Service orientation became a mediator between Islamic banks' growth and organisational climate. The analysis result of the second model captured the joint meetings among the Sharia Supervisory Board (SSB), Board of Commissioners (BOC), and Board of Directors (BOD) have positive significance in determining the growth of Islamic banks in Indonesia. All board members' meetings will enhance Islamic banks' quality, strengthening their supervision. Structural capital (SCE) and relational capital (RCE) have significant value for intellectual capital traits, negatively affecting profit growth. Human capital has a significant impact only on Islamic banks' revenue growth in Indonesia. This study contributes to the Islamic banking literature on organisational growth and its contingent factors for Indonesian Islamic banks. It also provides significant insight and suggestions to the regulators and policymakers of Islamic banks, such as the Financial Service Authority (Otoritas Jasa Keuangan) and Bank Indonesia. This study contributes to the new discussion regarding Indonesian Islamic banks' organisational growth. It provides significant insight and suggestions to the regulators and policymakers of Islamic banks, such as the Financial Service Authority (Otoritas Jasa Keuangan) and Bank Indonesia. In addition, the results of this study impact the area of organisational growth for further research by academicians, researchers and practitioners.